Human Sperm Cells After Purification Using SCLB Can Be Stored at 4o, -20o, or -80oC Before Small RNA Isolation - Berliana Hamidah; Ashon Sa'adi; Rina Yudiwati (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2020)
There have been many studies about pre-analysis for sperm RNA examination which compared sperm purification methods, RNA isolation methods, sequencing methods, and semen storage before analysis. However, there is a lack of studies that determine the ideal storage temperature after sperm cell purification before RNA analysis, especially small RNA analysis. The aim of this study was to determine the preferred storage temperature for human sperm cells after sperm purification using Somatic Cell Lysis Buffer (SCLB) before sperm small ribonucleic acid (RNA) isolation and analysis. Thisstudy was a true laboratory experiment using the post-test only control group design. The samples  were 13 fresh human semen that has been purified using SCLB. The sperm cells were then diluted and divided into four aliquots with different treatments. The first aliquot that served as a control group was immediately purified while the other three aliquots were 0 0 0 stored for seven days at different temperatures as follows: 4 C, -20 , and -80 C. After the small RNA isolation, RNA level between each group was compared. Micro volume spectrophotometer measured RNA level. The median of small RNA6 yields of the control group was 49.8 (5.33-522.46) ng/10 sperm cells. There was no significant difference in median of small RNA yields of the control group and that of other groups. The median of the other groups with storage temperature 0 0 0 6 of 4 C, -20 , and -80 C was 41.09 (7.03-1448.31), 65.95 (7.99-301.16), and 76.42 (10.45-434.25) ng/10 sperm cells, respectively (p-value= 0.314; Î±=5%). This condition suggested that after purification using SCLB, human sperm cells can be 0 0 0 stored at temperatures of 4 C, -20 , or -80 C for seven days, depending on each laboratory facility.